Feedforward Control of Gear Mesh Vibration Using Piezoelectric Actuators. (1994) - Montague, Gerald T.; Kascak, Albert F.; Palazzolo, Alan; Manchala, Daniel; Thomas, Erwin
Abstract : This article presents a novel means for suppressing gear mesh related vibrations. The key components in this approach are piezoelectric actuators and a high-frequency, analog feed forward controller. Test results are presented and show up to a 70% reduction in gear mesh acceleration and vibration control up to 4500 Hz. The principle of the approach is explained by an analysis of a harmonically excited, general linear vibratory system.